MIF Promotes Classical Activation and Conversion of Inflammatory Ly6C(high) Monocytes into TipDCs during Murine Toxoplasmosis - Ruiz-Rosado, Juan de Dios (Mediators Inflamm, 2016)
Macrophage migration inhibitory factor (MIF) mediates immunity against Toxoplasma gondii infection by inducing inflammatory cytokines required to control the parasite replication. However, the role of this inflammatory mediator in the cell-mediated immune response against this infection is still poorly understood. Here, we used T. gondii-infected WT and Mif (−/−) mice to analyze the role of MIF in the maturation of CD11b(+) and CD8α (+) dendritic cells (DCs). We found that MIF promotes maturation of CD11b(+) but not CD8α (+) DCs, by inducing IL-12p70 production and CD86 expression. Infected Mif (−/−) mice showed significantly lower numbers of TNF and inducible nitric oxide synthase- (iNOS-) producing DCs (TipDCs) compared to infected WT mice. The adoptive transfer of Ly6C(high) monocytes into infected WT or Mif (−/−) mice demonstrated that MIF participates in the differentiation of Ly6C(high) monocytes into TipDCs. In addition, infected Mif (−/−) mice display a lower percentage of IFN-γ-producing natural killer (NK) cells compared to WT mice, which is associated with reducing numbers of TipDCs in Mif (−/−) mice. Furthermore, administration of recombinant MIF (rMIF) into T. gondii-infected Mif (−/−) mice restored the numbers of TipDCs and reversed the susceptible phenotype of Mif (−/−) mice. Collectively, these results demonstrate an important role for MIF inducing cell-mediated immunity to T. gondii infection.